Effects of L-arginine Supplementation and Aerobic Training on Hemodynamic Indices of Obese Men - Jahani, Majid; Nabilpour, Maghsoud; Campillo, Rodrigo Ramirez (International Journal of Sport Studies for Health, 2019)
Background: L-arginine is a precursor to nitric oxide, which can affect some hemodynamic indices. Objectives: The purpose of this study was to investigate the effect of one-month aerobic training with and without supplementation of L-arginine on hemodynamic indices in obese men. Methods: A quasi-experimental double-blind, study was carried out. Subjects (age, 30 - 45 years; BMI, 38 - 40 kg.m-2) were randomly assigned to an exercise and L-arginine supplementation group (n = 10) and placebo group (n = 10). Before and after four weeks of aerobic exercise (three 90 - 120 min sessions per week at 65% - 85% of maximal heart rate), systolic and diastolic blood pressure, and rate pressure product (RPP) were measured at rest. The analysis of variance was used to determine the interaction between the two factors of exercise and supplementation of L-arginine on the dependent variables at P < 0.05. Results: Four weeks of aerobic exercise reduced the RPP in both groups (P ≤ 0.05), while the L-arginine group significantly reduced systolic blood pressure (116.6 ± 3.40), diastolic blood pressure (76 ± 2.29) and RPP (8918.2 ± 722.86). Conclusions: L-arginine supplementation along with four weeks of aerobic exercise can be effective in controlling hypertensive of obese men.